2013
DOI: 10.1177/2158244013503837
|View full text |Cite
|
Sign up to set email alerts
|

Applying the UTAUT to Understand Factors Affecting the Use of English E-Learning Websites in Taiwan

Abstract: The evolution of the Internet diminishes learning's limits on time and location and attracts more and more students to learning websites or online learning environments to pursue their chosen studies. The purpose of this study is to explore Taiwanese college students' needs for English E-learning websites. Accordingly, this paper uses the unified theory of acceptance and use of technology to investigate and explain Taiwanese college students' acceptance of English E-learning websites. After analysis, the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
224
2
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(270 citation statements)
references
References 25 publications
32
224
2
12
Order By: Relevance
“…Most e-learning systems provides services for searching, downloading, and delivering content (Tan, 2013a;Tan, 2013b;Tan, 2017a). They also provide e-users with various learning tools, such as systems, e-books, audio files, econtent, and videos to enhance their teaching and learning performance.…”
Section: E-learning and E-assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Most e-learning systems provides services for searching, downloading, and delivering content (Tan, 2013a;Tan, 2013b;Tan, 2017a). They also provide e-users with various learning tools, such as systems, e-books, audio files, econtent, and videos to enhance their teaching and learning performance.…”
Section: E-learning and E-assessmentmentioning
confidence: 99%
“…For example, Yoo, Han, and Huang (2012) found that employers in South Korea were positively influenced by factors such as effort expectancy and attitude towards e-learning in Table 2. Disadvantages and Advantages of Traditional and E-learning Approaches (Zhang et al, 2004;Tan, 2013a;Tan, 2013b;Tan, 2015) Traditional approaches E-learning approaches Advantages ◎ Familiar to both teachers and students ◎ Direct feedback ◎ Cultivation of a social community ◎ Motivates users ◎ User-centred and self-paced ◎ Place-and time-flexible ◎ Potentially provided to universal learners ◎ Cost-effective for users ◎ Archival ability for information resharing and reusing Disadvantages ◎ Teacher-centred ◎ Place-and time-limited ◎ More expensive (learner resources and teacher wages)…”
Section: E-learning and E-assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As a matter of fact, the Taiwan Ministry of Education (MOE) has initiated an advanced project for the purposes of enhancing English proficiency through e-learning since 2002, so that all Taiwanese people could learn without the constraints of time and space. To carry out this project numerous universities in Taiwan develop e-learning environments for English as a foreign language (EFL) courses (Spence & Liu, 2013;Tan, 2013;. To cope with the rising trend of ubiquitous e-learning, English teachers thus need to understand how to create effective English instruction through e-learning technologies with the goal of preparing students for the new information society as well as cultivating students with good English proficiency in order to utilize this global language wisely in future working environments.…”
Section: Introductionmentioning
confidence: 99%